Contribution to Indian economic history / edited by Tapan Ray Chaudhuri - "Ray Chaudhauri, Tapan.( ed.)" (Calcutta, 1960)
This book covers the following topics Banking in Mughal India; Agrarian structure in U.P. in the late 18th and early 19 century; The introduction of the Taluqdari system in Outh; An enquiry into the conditions of the agricultural classes in India,1888; Survey of Russian per-revolutionary and Soviet studies on modern in Indian economic history; Historical approach and under development economies; Some recent writing on the British Indian economic history etc.
Keywords: Economic history